2004
DOI: 10.1111/j.1365-2788.2003.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

An analogue assessment of repetitive hand behaviours in girls and young women with Rett syndrome

Abstract: Overall, environmental manipulations had relatively limited effects on repetitive hand behaviours. Repetitive hand behaviour in Rett syndrome may be maintained by automatic reinforcement or neurochemical processes and may not be primarily influenced by contingent reinforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The correlation between the extents of hand stereotypies and adult attention was insignificant and there were no consistent associations between hand stereotypies and adult attention revealed in the concurrent or sequential lag analyses. This apparent independence from environmental influence is consistent with the findings of Wales et al (2004) who demonstrated that the hand stereotypies of eight girls with RTT were not susceptible to environmental manipulation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The correlation between the extents of hand stereotypies and adult attention was insignificant and there were no consistent associations between hand stereotypies and adult attention revealed in the concurrent or sequential lag analyses. This apparent independence from environmental influence is consistent with the findings of Wales et al (2004) who demonstrated that the hand stereotypies of eight girls with RTT were not susceptible to environmental manipulation.…”
Section: Discussionsupporting
confidence: 91%
“…Oliver et al (1993) found that the function of the self-injury of a child with RTT was to terminate social contact, whereas Iwata et al (1986) concluded that the hand biting of two individuals was independent of environmental circumstances and appeared to be self-stimulatory. Wehmeyer et al (1993); Roane et al (2001) and Wales et al (2004) conducted functional assessments of hand stereotypies. All but one analysis suggested that occurrence was at a high rate and unaffected by environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, we contend that repetition is a trivial criterion for classifying behaviors~in the same way as a construct like "sensory dysfunction" is comprehensively uninformative about autistic perceptual and behavioral atypicalities, see Rogers & Ozonoff, 2005!, and that no statement regarding repetitive behaviors as a single entity should be enounced: a putative specificity of repetitive behaviors toward other neurodevelopmental conditions should be investigated separately for each individual behavior e.g., lateral glance!. For example, repetitive hand behaviors appear in both autism and Rett syndrome, but a further examination of hand movement in Rett syndrome has resulted in a finer grained description of this behavior, now included in the phenotype of this conditioñ Wales, Charman, & Mount 2004!. Similarly, the current study provides the preliminary finegrained characterization necessary to study the specificity of atypical visual behaviors to autism compared to other neurodevelopmental disorders.…”
Section: Specificity Of Avebios Toward Typical and Atypical Developmentmentioning
confidence: 99%
“…With respect to the assessment of RS cognitive functions, a focus on two main areas can be identified in the literature: eye gaze communication (Woodyatt and Ozanne, 1992, 1997; von Tetzchner et al, 1996; von Tetzchner, 1997; Umansky and Watson, 1998; Sandberg et al, 2000; Umansky et al, 2001) and communication by means of a functional analysis of behavior patterns (Roane et al, 2001; Baschina et al, 2002; Cass et al, 2003; Sarimski, 2003; Umansky et al, 2003; Wright et al, 2003; Wales et al, 2004), such as abnormal breathing patterns, hand stereotypies, etc. The overall picture that results is that girls with RS are classified within the third or the fourth stage of sensorimotor intelligence, corresponding, respectively, to a mental age of 4–8 and 8–12 months (Olsson and Rett, 1985, 1990; Olsson, 1987) or exceptionally in the transition to the pre-operatory stage (Lindberg, 1988).…”
Section: Introductionmentioning
confidence: 99%